2007
DOI: 10.1152/japplphysiol.01315.2006
|View full text |Cite
|
Sign up to set email alerts
|

Severe hemodilutional anemia increases cerebral tissue injury following acute neurotrauma

Abstract: Anemia may worsen neurological outcomes following traumatic brain injury (TBI) by undefined mechanisms. We hypothesized that hemodilutional anemia accentuates hypoxic cerebral injury following TBI. Anesthetized rats underwent unilateral TBI or sham injury (n > or = 7). Target hemoglobin concentrations between 50 and 70 g/l were achieved by exchanging 40-50% of the blood volume (1:1) with pentastarch. The effect of TBI, anemia, and TBI-anemia was assessed by measuring brain tissue oxygen tension (Pbr(O(2))), re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
55
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 79 publications
(56 citation statements)
references
References 51 publications
(69 reference statements)
1
55
0
Order By: Relevance
“…7 Evaluation of co-oximetry data (delta hemoglobin and methemoglobin) is presented from five previously published experimental studies. 13,[65][66][67]95 An expected strong positive correlation was observed between the change in hemoglobin and blood oxygen content in control (no hemodilution) or 50% hemodiluted rats (positive control, Upper Panel). A positive correlation was also observed between the change in hemoglobin and methemoglobin levels, suggesting that hemodilutional anemia led to a proportional increase in methemoglobin levels (Lower Panel)…”
Section: Clinical Relevance Of Understanding Nos-mediated Cardiovascumentioning
confidence: 87%
See 3 more Smart Citations
“…7 Evaluation of co-oximetry data (delta hemoglobin and methemoglobin) is presented from five previously published experimental studies. 13,[65][66][67]95 An expected strong positive correlation was observed between the change in hemoglobin and blood oxygen content in control (no hemodilution) or 50% hemodiluted rats (positive control, Upper Panel). A positive correlation was also observed between the change in hemoglobin and methemoglobin levels, suggesting that hemodilutional anemia led to a proportional increase in methemoglobin levels (Lower Panel)…”
Section: Clinical Relevance Of Understanding Nos-mediated Cardiovascumentioning
confidence: 87%
“…In support of this hypothesis, a review of data from previously published hemodilution studies has demonstrated a positive correlation between the reduction in absolute hemoglobin and the % increase in MetHb level ( Figure 7). 13,[65][66][67]95 In addition, the increase in MetHb occurred after hemodilution with either 5% albumin or 10% pentastarch, suggesting that the effect was independent of the type of colloid used (Figure 8). In these experiments, the amount of MetHb formed was proportional to the degree of hemodilution with 5% albumin, suggesting a causal link between blood oxygen content and the amount of MetHb formed.…”
Section: Potential Sources Of Vascular No During Hemodilutionmentioning
confidence: 98%
See 2 more Smart Citations
“…Available data regarding safe hematocrit levels for the nervous system derive mostly from experimental studies and a few clinical studies that associate anemia with neurological outcome after cardiopulmonary bypass (Hare et al, 2007). In healthy young human subjects, ANH to hemoglobin of 5.7 g/dL elicited subtle cognitive dysfunction and memory deficits that were reversible with erythrocyte transfusion or increase in oxygen concentration (Weiskopf et al, 2002).…”
Section: Impact Of Anh On Brainmentioning
confidence: 99%